2023
DOI: 10.3390/cells12010198
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Association between Diabetic Neuropathy and Vitamin D in Emirati Patients with Type 2 Diabetes Mellitus

Abstract: (1) Background: Vitamin D deficiency is a common public health problem in the United Arab Emirates (UAE) and globally, and interestingly, improvements in diabetic neuropathy after taking Vitamin D supplementation for a short time have been reported. Despite living in a country that is sunny all year round, hypovitaminosis D, indicated by an obvious low serum vitamin D level, has been recurrently noted in the UAE, as well as in the surrounding Arabian Gulf countries. This problem is receiving much attention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, vitamin D may enhance the function of calcium channels, which are important for nerve conduction and neurotransmission [ 57 ]. Regarding diabetic macroangiopathy, vitamin D is involved in reducing chronic inflammation and oxidative stress, which are major factors in endothelial dysfunction, atherosclerosis, and modulating angiogenesis, which is impaired in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vitamin D may enhance the function of calcium channels, which are important for nerve conduction and neurotransmission [ 57 ]. Regarding diabetic macroangiopathy, vitamin D is involved in reducing chronic inflammation and oxidative stress, which are major factors in endothelial dysfunction, atherosclerosis, and modulating angiogenesis, which is impaired in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is a growing global health problem, even in countries like the United Arab Emirates, which receives plenty of sunshine yearly (18). This implies that the vitamin D produced by the sun's ultraviolet rays is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence highlights an early treatment window for patients with T2DM and the possibility that vitamin D supplementation may prevent the development of DSPN. A previous retrospective study found that vitamin D levels in patients with T2DM and DSPN were one-third lower than those without DSPN, suggesting that vitamin D may affect DSPN progression (18). Furthermore, clinical studies have shown that HDVD supplementation can significantly reduce the pain score of DSPN, reduce demyelination, improve axonal regeneration, and even improve the quality of life of patients with DSPN (33,34,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation